Functional properties of α-lactalbumin and β-lactoglobulin - Zoran Herceg; Vesna Lelas; Anet Režek (Mljekarstvo)
Whey proteins are commonly used in the food industry due to their nutritive value and functional properties. The most important functional properties of whey proteins are solubility, viscosity, water holding capacity, emulsification and foaming. The aim of this study was to determine functional properties of main whey protein fractions (α-lactalbumin and β-lactoglobulin) which have the biggest influence on the functional properties of whey proteins. Particle size analysis and specific area of α-lactalbumin and β-lactoglobulin were performed by «Mie – theory» of «light scatering» using «Malvern Mastersizer X». The results of this analysis have shown that β-lactoglobulin had higher particle size and specific area than α-lactalbumin.By examining functional properties (solubility, dispersibility, emulsifiying properties – emulsion activity index (EAI) and emulsion stability index (ESI) and foaming properties) of α-lactalbumin and β-lactoglobulin, it has been established that β-lactoglobulin has higher solubility, dispersibility, emulsifiying properties as well as foaming properties than α-lactalbumin. Rheological properties of protein suspensions were determined by rotational viscosimeter, Brookfiel DV-III at temperature 25°C. Rheological parameters, flow behavior indeks (n) and consistency coefficient (k) were determined by the power-law model. The results of investigation have shown that 10% suspenzion of α-lactalbumin and β-lactoglobulin are non-Newtonian fluids and they exhibited pseudoplastic properties.